Permeability of Native and Target Language to International Learners’ Descriptive Composition: A Case Study - Saswati, Risna; Puspitasari, Intan (STIBA IEC JAKARTA, 2025)
This study is to investigate the interlanguage errors that the learners committed in their Indonesian descriptive paragraphs. It does not only shed light on the categories of interlanguage errors but also the sources of the interlanguage errors found in learners’ writing. The research method employed for this study is a descriptive qualitative method that applies the theories of error taxonomy from Dulay & Burt (1982) and Brown (2007). The participants of this study are international students learning Indonesian in Basic Indonesian class. The data are taken from their descriptive writing. The result reveals that the most common category of error the students committed is the spelling and diction used. The source of errors mostly found is interference from English since they are still learning English.